Cellulose paper-based polymer solid electrolyte as well as preparation method and application thereof

By preparing cellulose paper-based polymer solid electrolyte, the problems of low lithium ion conductivity and poor interface contact in solid lithium ion batteries are solved, efficient lithium ion transportation is achieved and the internal impedance of the battery is reduced, and the overall performance and safety of the battery are improved.

CN120127212APending Publication Date: 2025-06-10CHINA NAT PULP & PAPER RES INST CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510455399.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

In solid-state lithium-ion batteries, the low conductivity of lithium-ion batteries and poor solid-solid interface contact between the solid-state electrolyte and the electrode leads to low lithium-ion transport efficiency and increased interface impedance.

Method used

The cellulose paper-based polymer solid electrolyte is used. The preparation method includes mixing N-methylacetamide and lithium bistrifluoromethanesulfonimide to form a low-eutectic solvent, and then mixing it with polyethylene glycol eglylate, acrylamide and a thermal initiator to form a low-cosoluble polymer electrolyte precursor, and finally immersing the cellulose paper in the precursor and performing hot press polymerization to form a cellulose paper-based polymer solid electrolyte.

Benefits of technology

It improves the conductivity of lithium ions, reduces the interface impedance, enhances the overall performance and charge and discharge efficiency of the battery, and avoids the risk of flammability of liquid electrolytes and the formation of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120127212A_ABST
    Figure CN120127212A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-solid-state lithium metal batteries, in particular to a cellulose paper-based polymer solid electrolyte as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing N-methylacetamide and lithium bis (trifluoromethanesulfonyl) imide to obtain a eutectic solvent; the preparation method comprises the following steps: mixing a eutectic solvent, polyethylene glycol oxalate, acrylamide and a thermal initiator to obtain a eutectic polymer electrolyte precursor; and soaking cellulose paper in the eutectic polymer electrolyte precursor, and carrying out hot-pressing polymerization to obtain the cellulose paper-based polymer solid electrolyte. The cellulose paper-based polymer solid electrolyte prepared by the invention is soft in texture and can be better attached to an electrode, the problem of poor contact between the electrode and an electrolyte interface is solved, and the interface impedance is reduced by fusing the characteristics of low viscosity and high conductivity of the eutectic solvent and the supporting effect of the cellulose paper; the ion transmission efficiency is improved, and conditions are provided for long-term stable circulation of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state lithium metal batteries, and particularly relates to a cellulose paper-based polymer solid electrolyte, a preparation method thereof, and an application thereof. Background Art

[0002] In recent years, the rapid development of lithium-ion batteries has promoted the sustainable development of clean and green energy. However, the uncontrollable growth of lithium dendrites will penetrate the separator, thereby triggering serious safety problems, including short circuits, thermal runaway, and even violent explosions, which are related to the flammable characteristics of liquid electrolytes. Solid electrolytes are materials with broad application prospects, especially in the fields of energy storage, transmission, and conversion. In recent years, with the continuous improvement of requirements for energy efficiency and safety, solid electrolytes, as a new type of material to replace traditional liquid electrolytes, have attracted wide attention in society. Compared with liquid electrolytes, solid electrolytes not only have better thermal stability and chemical stability, but also can effectively avoid the leakage and flammable risks existing in liquid electrolytes. Therefore, solid electrolytes have great application potential in the fields of lithium-ion batteries, solid-state batteries, electrochemical sensors, and superconducting materials.

[0003] However, during the application process of solid electrolytes, there are still two major problems: one is the low lithium-ion conductivity, which directly leads to the low efficiency of lithium-ion transportation; the other is the poor solid-solid interface contact between the solid electrolyte and the electrode, which thus causes an increase in interface impedance. Summary of the Invention

[0004] Aiming at the problems existing in the prior art, the present invention provides a cellulose paper-based polymer solid electrolyte, a preparation method thereof, and an application thereof. The present invention uses N-methylacetamide and lithium bis(trifluoromethanesulfonyl)imide as raw materials to obtain a eutectic solvent. Subsequently, polyethylene glycol oxalate, acrylamide, and a thermal initiator are placed in the eutectic solvent to obtain a eutectic polymer electrolyte precursor; finally, cellulose paper is immersed in the eutectic polymer electrolyte precursor, taken out, and hot-pressed and polymerized to obtain a cellulose paper-based polymer solid electrolyte. The cellulose paper-based polymer solid electrolyte prepared by the present invention is soft in texture and can better fit the electrode. It not only overcomes the problem of poor interface contact between the electrode and the electrolyte, but also reduces the interface impedance and improves the ion transport efficiency by integrating the characteristics of low viscosity and high conductivity of the eutectic solvent and the supporting effect of cellulose paper, providing conditions for the long-term stable cycling of the battery.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The first object of the present invention is to provide a preparation method of a cellulose paper-based polymer solid electrolyte, comprising the following steps: S1. Mix N-methylacetamide and lithium bis(trifluoromethanesulfonyl)imide. N-methylacetamide serves as a hydrogen bond donor, and lithium bis(trifluoromethanesulfonyl)imide serves as a hydrogen bond acceptor. They form a eutectic solvent through hydrogen bonding.

[0006] S2. Mix the eutectic solvent, polyethylene glycol oxalate, acrylamide, and a thermal initiator to obtain a eutectic polymer electrolyte precursor.

[0007] The mass ratio of polyethylene glycol oxalate, acrylamide to the eutectic solvent is 0.98 - 1.02:0.99 - 1.02:9.95 - 10.02. Among them, if the mass ratio of the eutectic solvent is too high or too low, it will have a significant impact on its physical and chemical properties and application performance. Specifically, there are five aspects: First, the deviation of the eutectic temperature of the eutectic solvent; second, the change in the viscosity of the eutectic solvent; third, the decrease in the solubility of the eutectic solvent; fourth, the decrease in ionic conductivity, which affects the ionic transport efficiency and thus the battery performance; fifth, the decrease in thermal stability and chemical stability, which further affects the use stability of the eutectic solvent.

[0008] S3. Immerse the cellulose paper in the eutectic polymer electrolyte precursor, then take it out and perform hot pressing polymerization. Under the action of the thermal initiator, the double bond of acrylamide undergoes free radical polymerization to form polyacrylamide. At the same time, the eutectic solvent is in-situ encapsulated in the cross-linked network structure formed by hydrogen bonding between polyethylene glycol oxalate and polyacrylamide to obtain a cellulose paper-based polymer solid electrolyte.

[0009] Preferably, the mass ratio of N-methylacetamide to lithium bis(trifluoromethanesulfonyl)imide is 2.96 - 3.03:2.94 - 2.97. Among them, if the mass ratio of N-methylacetamide to lithium bis(trifluoromethanesulfonyl)imide is too high or too low, it will affect the lithium ion transport. When the content of lithium bis(trifluoromethanesulfonyl)imide is small, it cannot actively provide lithium ions during battery operation. When the content of lithium bis(trifluoromethanesulfonyl)imide is too large, the high concentration of lithium bis(trifluoromethanesulfonyl)imide will affect the lithium ion transport rate, thus affecting the cycle performance of the battery.

[0010] Preferably, the mass ratio of polyethylene glycol oxalate, acrylamide to the eutectic solvent is 1:1:10.

[0011] Preferably, the conditions for hot pressing polymerization are: hot pressing polymerization at 4.5 MPa - 5 MPa and 80 °C - 90 °C for 40 min - 50 min.

[0012] Preferably, the thermal initiator is selected from azobisisobutyronitrile or ammonium persulfate.

[0013] Preferably, the dosage of the thermal initiator accounts for 0.98% to 1.01% of the mass of the deep eutectic solvent. If the dosage of the thermal initiator is lower than 0.98%, the polymerization reaction rate is slow, the crosslinking density is low, and there is a problem of incomplete curing due to insufficient initiation. If the dosage of the thermal initiator is higher than 1.01%, the polymerization reaction rate is too fast, which affects the uniformity and initiates side reactions, affecting the performance of the cellulose paper-based polymer solid electrolyte.

[0014] The second object of the present invention is to provide a cellulose paper-based polymer solid electrolyte prepared by the above preparation method.

[0015] Preferably, the thickness of the cellulose paper-based polymer solid electrolyte is 70 μm to 75 μm.

[0016] Preferably, the surface of the cellulose paper-based polymer solid electrolyte is flat and smooth, and the cross-section has a sandwich structure. The sandwich structure consists of an intermediate layer of cellulose film and a polymer solid electrolyte, and the polymer solid electrolyte is located on both sides of the intermediate layer.

[0017] The third object of the present invention is to provide a solid-state lithium metal battery, which consists of a negative electrode case, a shrapnel, a gasket, a negative lithium sheet, the above-mentioned cellulose paper-based polymer solid electrolyte, a positive electrode sheet, and a positive electrode case.

[0018] Preferably, the solid-state lithium metal battery is prepared according to the following steps: in a glove box filled with argon, sequentially place the negative electrode case, the shrapnel, the gasket, the negative lithium sheet, cover the solid polymer electrolyte on the negative lithium sheet, then put in the positive electrode sheet, cover the positive electrode case and press the battery tightly.

[0019] Preferably, the positive electrode sheet is selected from a positive lithium sheet or a lithium iron phosphate electrode sheet.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The present invention provides a preparation method of a cellulose paper-based polymer solid electrolyte. By mixing N-methylacetamide and lithium bis(trifluoromethanesulfonyl)imide, with N-methylacetamide as a hydrogen bond donor and lithium bis(trifluoromethanesulfonyl)imide as a hydrogen bond acceptor, a deep eutectic solvent is obtained through hydrogen bond interaction. Then, the deep eutectic solvent, polyethylene glycol diacrylate, acrylamide, and a thermal initiator are mixed to obtain a low-melting polymer electrolyte precursor. The cellulose paper is immersed in the low-melting polymer electrolyte precursor. The cellulose paper serves as a substrate and can play a good supporting role. Through hot pressing polymerization, under the action of the thermal initiator, the double bonds of acrylamide undergo free radical polymerization to form polyacrylamide. At the same time, the deep eutectic solvent is in-situ encapsulated in the crosslinked network structure formed by hydrogen bond interaction between polyethylene glycol diacrylate and polyacrylamide, obtaining a cellulose paper-based polymer solid electrolyte. The cellulose paper-based polymer solid electrolyte prepared by the present invention can not only solve the problems of poor ionic conductivity and poor interfacial contact in the existing solid-state batteries, but also improve the lithium ion conductivity.

[0021] 2. The cellulose paper-based polymer solid electrolyte prepared by the preparation method of the present invention has the characteristics of being non-flammable, high ionic conductivity, and a wide electrochemical window for resisting temperature changes. This is because the deep eutectic solvent is composed of the low-melting salt lithium bis(trifluoromethanesulfonyl)imide and the solvent N-methylacetamide, and its melting point is much lower than that of traditional electrolyte solutions, and it can remain liquid within a wide temperature range. This characteristic not only endows the cellulose paper-based polymer solid electrolyte with high ionic conductivity but also ensures its stable electrochemical performance under different temperature conditions, that is, a wide electrochemical window. At the same time, the deep eutectic solvent has high thermal stability and non-flammability, further avoiding the risk of flammability. In addition, during the polymerization process of the deep eutectic polymer electrolyte precursor, a solid network structure will be formed, and this network structure endows it with higher mechanical strength than liquid electrolytes, which can effectively prevent the leakage of the cellulose paper-based polymer solid electrolyte and improve the safety of the battery. The deep eutectic solvent is composed of the hydrogen bond donor N-methylacetamide and the lithium bis(trifluoromethanesulfonyl)imide acceptor, and has rich ion conduction channels, and its ionic conductivity can reach the level of liquid electrolytes, that is, 10 -3 S / cm~10 -2 S / cm. Incorporating the deep eutectic solvent into the cellulose paper-based polymer electrolyte can significantly improve the conductivity of the solid electrolyte.

[0022] 3. The cellulose paper-based polymer solid electrolyte of the present invention is soft in texture and has self-adaptability, and can better fill the microscopic uneven areas on the electrode surface, thereby solving the problem of poor solid-solid interface contact between the solid electrolyte and the electrode and reducing the interface impedance. In addition, the cellulose paper-based polymer solid electrolyte of the present invention incorporates the characteristics of the deep eutectic solvent. With low viscosity and high conductivity, it effectively reduces the ion migration resistance, thereby reducing the internal resistance of the lithium metal battery and significantly improving the overall efficiency and charge-discharge efficiency of the lithium metal battery.

[0023] 4. The cellulose paper-based polymer solid electrolyte of the present invention has excellent interfacial compatibility and can inhibit the growth of lithium dendrites. Its viscosity and structural characteristics promote the uniform distribution of the electric field in the lithium metal battery, effectively preventing the uneven deposition of lithium ions on the surface of the lithium metal electrode, thereby reducing the formation of lithium dendrites and avoiding potential safety hazards such as short circuits and thermal runaway, and improving the safety and cycle life of the lithium metal battery. At the same time, a stable solid electrolyte interface, that is, a SEI film, can be formed between the cellulose paper-based polymer solid electrolyte and the lithium metal battery electrode, which can effectively prevent the direct contact between the lithium metal and the cellulose paper-based polymer solid electrolyte, reduce side reactions, and further improve the cycle stability and life of the lithium metal battery. Description of the Drawings

[0024] Figure 1Fourier transform infrared spectra of the cellulose paper-based polymer solid electrolyte and cellulose paper prepared in Example 1.

[0025] Figure 2 SEM image of the surface of the cellulose paper-based polymer solid electrolyte prepared in Example 1.

[0026] Figure 3 SEM image of the cross-section of the cellulose paper-based polymer solid electrolyte prepared in Example 1.

[0027] Figure 4 Visual image of the flexibility of the cellulose paper-based polymer solid electrolyte prepared in Example 1. Among them, a is before folding, b is the visual image of folding flexibility, c is the visual image of refolding flexibility, and d is the visual image of unfolding flexibility.

[0028] Figure 5 Thermal stability test chart of the cellulose paper-based polymer solid electrolyte prepared in Example 1. Among them, a is the thermal stability test chart at 25°C for 30 min, b is the thermal stability test chart at 100°C for 30 min, c is the thermal stability test chart at 150°C for 30 min, and d is the thermal stability test chart at 25°C for 30 min.

[0029] Figure 6 Impedance electrochemical test chart of the Li symmetric battery assembled with the cellulose paper-based polymer solid electrolyte prepared in Application Example 1.

[0030] Figure 7 Lithium ion transference number curve chart of the Li symmetric battery assembled with the cellulose paper-based polymer solid electrolyte prepared in Application Example 1. Among them, the inset is the enlarged Nyquist curve at different temperatures.

[0031] Figure 8 Conductivity test chart at different temperatures of the asymmetric battery assembled with the cellulose paper-based polymer solid electrolyte prepared in Application Example 1. Among them, the inset is the EIS chart before and after the it test.

[0032] Figure 9 Tafel curve chart of the Li symmetric battery assembled with the cellulose paper-based polymer solid electrolyte prepared in Application Example 1.

[0033] Figure 10 LSV curve chart of the Li-SS battery assembled with the cellulose paper-based polymer solid electrolyte prepared in Application Example 1.

[0034] Figure 11 Long cycle charge and discharge test chart of the Li symmetric battery assembled with the cellulose paper-based polymer solid electrolyte prepared in Application Example 1. Detailed implementation mode

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the data in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.

[0036] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be obtained through market purchase or prepared by existing methods. Among them, lithium bis(trifluoromethanesulfonyl)imide is LiTFSI.

[0037] In the prior art, although solid electrolytes are highly anticipated due to their significant advantages, at the practical application level, they still need to overcome a series of major challenges. Specifically, the main problems faced by solid electrolytes include low lithium ion conductivity, which directly limits the lithium ion transport efficiency; at the same time, there is a poor solid-solid interface contact between the solid electrolyte and the electrode, which significantly increases the interface impedance and affects the overall performance of the battery.

[0038] In view of the above technical defects existing in the prior art, the present invention provides a preparation method of a cellulose paper-based polymer solid electrolyte, which includes the following steps: mixing N-methylacetamide and lithium bis(trifluoromethanesulfonyl)imide, using N-methylacetamide as a hydrogen bond donor and lithium bis(trifluoromethanesulfonyl)imide as a hydrogen bond acceptor, and obtaining a eutectic solvent through hydrogen bond interaction; mixing the eutectic solvent, polyethylene glycol diacrylate, acrylamide and a thermal initiator to obtain a eutectic polymer electrolyte precursor; soaking the cellulose paper in the eutectic polymer electrolyte precursor, then taking it out and performing hot pressing polymerization. Under the action of the thermal initiator, the double bond of acrylamide undergoes free radical polymerization to form polyacrylamide; at the same time, the eutectic solvent is in-situ encapsulated in the cross-linked network structure formed by hydrogen bond interaction between polyethylene glycol diacrylate and polyacrylamide to obtain a cellulose paper-based polymer solid electrolyte.

[0039] The cellulose paper-based polymer solid electrolyte prepared by the present invention has a soft texture and can better fit the electrode. It not only overcomes the problem of poor interface contact between the electrode and the electrolyte, but also reduces the interface impedance and improves the ion transport efficiency by integrating the characteristics of low viscosity and high conductivity of the eutectic solvent and the supporting role of the cellulose paper, providing conditions for the long-term stable cycling of the battery.

[0040] The technical solution of the present invention will be further explained and illustrated below by examples, as specifically shown below: Example 1 A preparation method of a cellulose paper-based polymer solid electrolyte, comprising the following steps: S1. Mix N-methylacetamide and LiTFSI according to a mass ratio of 3:2.95 to obtain a eutectic solvent, denoted as DES.

[0041] S2. Add 0.6 g of polyethylene glycol oxalate and 0.6 g of acrylamide to 6 g of DES, stir and mix evenly to obtain a mixture. Heat and stir the mixture until it is completely melted. After LiTFSI is completely dissolved, add 0.06 g of thermal initiator AIBN to obtain a eutectic polymer electrolyte precursor.

[0042] S3. Immerse the cellulose paper in the eutectic polymer electrolyte precursor, then take it out and put the cellulose paper infiltrated with the precursor into a hot press for hot pressing polymerization under the conditions of 5 MPa and 85 °C to obtain a cellulose paper-based polymer solid electrolyte.

[0043] Example 2 A preparation method of a cellulose paper-based polymer solid electrolyte, comprising the following steps: S1. Mix N-methylacetamide and LiTFSI according to a mass ratio of 2.96:2.94 to obtain a eutectic solvent, denoted as DES.

[0044] S2. Add 0.578 g of polyethylene glycol oxalate and 0.584 g of acrylamide to 5.8 g of DES, stir and mix evenly to obtain a mixture. Heat and stir the mixture until it is completely melted. After LiTFSI is completely dissolved, add 0.0578 g of thermal initiator AIBN to obtain a eutectic polymer electrolyte precursor.

[0045] S3. Immerse the cellulose paper in the eutectic polymer electrolyte precursor, then take it out and put the cellulose paper infiltrated with the precursor into a hot press for hot pressing polymerization under the conditions of 5 MPa and 85 °C to obtain a cellulose paper-based polymer solid electrolyte.

[0046] Example 3 A preparation method of a cellulose paper-based polymer solid electrolyte, comprising the following steps: S1. Mix N-methylacetamide and LiTFSI according to a mass ratio of 3.03:2.97 to obtain a eutectic solvent, denoted as DES.

[0047] S2. Add 0.612 g of polyethylene glycol oxalate and 0.612 g of acrylamide to 6.1 g of DES, stir and mix evenly to obtain a mixture. Heat and stir the mixture until it is completely melted. After LiTFSI is completely dissolved, add 0.0606 g of thermal initiator AIBN to obtain a eutectic polymer electrolyte precursor.

[0048] S3. Immerse the cellulose paper in the deep eutectic polymer electrolyte precursor, then take it out and put the cellulose paper infiltrated with the precursor into a hot press for hot press polymerization at 4.5 MPa and 80 °C to obtain a cellulose paper-based polymer solid electrolyte.

[0049] In Examples 1 to 3 of the present invention, cellulose paper-based polymer solid electrolytes were all prepared and had parallel effects. Hereinafter, the cellulose paper-based polymer solid electrolyte prepared in Example 1 will be taken as an example for research: I. Battery assembly: Use the cellulose paper-based polymer solid electrolyte prepared in Example 1 as the electrolyte to assemble a battery: Taking the CR2032 button battery as an example, in a glove box filled with argon, successively place the negative electrode case, the shrapnel, the gasket, the negative lithium sheet, cover the cellulose paper-based polymer solid electrolyte on the negative lithium sheet, then put in the positive lithium sheet, cover the positive electrode case and press the battery tightly to obtain the battery.

[0050] Observe Figure 1 It is concluded that compared with the cellulose paper, the cellulose paper-based polymer solid electrolyte exhibits more abundant polar functional group characteristics, such as C-O, C=O, C-H, and C-N functional groups, indicating that the deep eutectic polymer electrolyte precursor has successfully combined with the cellulose paper to form a cellulose paper-based polymer solid electrolyte.

[0051] From Figure 2 It is concluded that the surface of the cellulose paper-based polymer solid electrolyte is flat, smooth and free of inhomogeneities, which can reduce the interfacial impedance between the electrolyte and the electrode.

[0052] From Figure 3 It is concluded that the cross-section of the cellulose paper-based polymer solid electrolyte presents a sandwich structure, which meets the expectation. The two sides are electrolyte layers polymerized from the deep eutectic polymer electrolyte precursor, and the middle is mainly composed of a film impregnated and solidified by cellulose paper. The thickness of the cellulose paper-based polymer solid electrolyte is about 70 μm.

[0053] In order to illustrate the key role of the physical properties of the cellulose paper-based polymer solid electrolyte in the battery, a visual effect display of the cellulose paper-based polymer solid electrolyte membrane was carried out.

[0054] From Figure 4It is concluded that when the cellulose paper-based polymer solid electrolyte is folded in half and then refolded, the overall structure remains intact, and it can also remain intact after being unfolded again. This indicates that the cellulose paper-based polymer solid electrolyte has great flexibility and mechanical properties. However, excellent thermal stability is the most important, especially under high-temperature conditions. If this stability cannot be maintained, it will lead to significant changes in the size of the battery electrolyte membrane, resulting in thermal runaway or catastrophic explosion.

[0055] It is concluded that Figure 5 the cellulose paper-based polymer solid electrolyte can maintain the structural integrity of the electrolyte membrane at 150 °C, and its excellent thermal stability enables it to evenly distribute the temperature and prevent localization.

[0056] To study the effect of the cellulose paper-based polymer solid electrolyte on the Li + conductive dynamic characteristics, measurement experiments of ionic conductivity and Li + transference number were carried out.

[0057] Figure 6 The EIS of the battery using the cellulose paper-based polymer solid electrolyte is shown. It is observed Figure 6 that a semicircle appears in the higher frequency range, which is related to the resistance value associated with charge transfer. The cellulose paper-based polymer solid electrolyte shows a reduced charge transfer resistance, i.e., R ct . This indicates that the cellulose paper-based polymer solid electrolyte has less resistance to Li + migration and a faster electrochemical reaction rate. In addition, the temperature-dependent ionic conductivity of the cellulose paper-based polymer solid electrolyte was evaluated using EIS.

[0058] It is concluded that Figure 7 the resistance of the cellulose paper-based polymer solid electrolyte at 25 °C is 36 Ω, and the ionic conductivity is 0.14 mS / cm. In addition, as the experimental temperature increases, the ionic conductivity increases. From the calculation of ionic conductivity, it can be seen that the cellulose paper-based polymer solid electrolyte has good ionic migration kinetics. In addition to ionic conductivity, t Li + is another key factor for high-performance lithium metal batteries.

[0059] It is concluded that Figure 8 using the Bruce-Vincent-Evans technique for the t Li +Research and calculations were carried out. It can be seen from the IT curve that the cellulose paper-based polymer solid electrolyte has excellent lithium ion transference number, significantly improving the effective transmission efficiency of lithium ions, which is extremely beneficial to the process of lithium ion insertion and extraction, and also promotes the stable operation of the electrode. In addition, the exchange current density, namely j 0 , was determined by means of the Tafel plot to evaluate the charge transfer kinetics at the electrode-electrolyte interface.

[0060] It was obtained from Figure 9 that the superior j of the cellulose paper-based polymer solid electrolyte 0 is 0.062 mA / cm², indicating that the charge transfer kinetics of the cellulose paper-based polymer solid electrolyte is also good.

[0061] It was obtained from Figure 10 that the LSV curve shows a wide electrochemical stability window of the cellulose paper-based polymer solid electrolyte, extending to 4.76 V, indicating that the cellulose paper-based polymer solid electrolyte has great potential for market application and can be used as the electrolyte of high-voltage batteries.

[0062] In order to further study the role of the cellulose paper-based polymer solid electrolyte in stabilizing the lithium metal anode, the present invention carried out a continuous lithium ion electroplating and stripping process at a current density of 0.1 mA / cm² and a capacity of 0.1 mAh / cm².

[0063] It was obtained from Figure 11 that the overpotential of the battery using the cellulose paper-based polymer solid electrolyte is stable, and the polarization phenomenon of the battery using the cellulose paper-based polymer solid electrolyte is still very small after continuous use for 100 h. Therefore, the cellulose paper-based polymer solid electrolyte realizes stable lithium electroplating and stripping.

[0064] In summary, the cellulose paper-based polymer solid electrolyte prepared by the present invention provides guidance for realizing stable cycling performance and high power density solid-state batteries.

[0065] It should be noted that when the present invention involves numerical ranges, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the adopted step methods are the same as those in the embodiments, in order to prevent repetition, the present invention describes the preferred embodiments. Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the appended claims are intended to be construed as including the preferred embodiments and all changes and modifications falling within the scope of the present invention.

Claims

1. A method for preparing a cellulose paper-based polymer solid electrolyte, characterized in that: The following steps are involved: N-methylacetamide and lithium bis(trifluoromethanesulfonyl)imide are mixed, wherein N-methylacetamide serves as a hydrogen bond donor and lithium bis(trifluoromethanesulfonyl)imide serves as a hydrogen bond acceptor, and a deep eutectic solvent is obtained through hydrogen bonding. Mixing a deep eutectic solvent, polyethylene glycol oxalate, acrylamide and a thermal initiator to obtain a deep eutectic polymer electrolyte precursor; The cellulose paper is immersed in a low eutectic polymer electrolyte precursor, then taken out and subjected to hot-pressing polymerization. Under the action of a thermal initiator, the double bonds of acrylamide undergo free radical polymerization to form polyacrylamide. At the same time, the low eutectic solvent is in situ encapsulated in a cross-linked network structure formed by polyethylene glycol oxalate and polyacrylamide through hydrogen bonding to obtain a cellulose paper-based polymer solid electrolyte.

2. The method for preparing a cellulose paper-based polymer solid electrolyte according to claim 1, characterized in that: The mass ratio of N-methylacetamide to lithium bis(trifluoromethanesulfonyl)imide is 2.96-3.03:2.94-2.

97.

3. The method for preparing a cellulose paper-based polymer solid electrolyte according to claim 1, characterized in that: The mass ratio of polyethylene glycol oxalate, acrylamide and low eutectic solvent is 0.98~1.02:0.99~1.02:9.95~10.

02.

4. The method for preparing a cellulose paper-based polymer solid electrolyte according to claim 1, characterized in that: The mass ratio of polyethylene glycol oxalate, acrylamide and low eutectic solvent is 1:1:

10.

5. The method for preparing a cellulose paper-based polymer solid electrolyte according to claim 1, characterized in that: The conditions of the hot press polymerization are: hot press polymerization at 4.5MPa~5MPa and 80℃~90℃ for 40min~50min.

6. The method for preparing a cellulose paper-based polymer solid electrolyte according to claim 1, characterized in that: The amount of thermal initiator used accounts for 0.98%~1.01% of the mass of the low eutectic solvent.

7. A cellulose paper-based polymer solid electrolyte, characterized in that: The cellulose paper-based polymer solid electrolyte is prepared by the preparation method according to any one of claims 1 to 6.

8. The cellulose paper-based polymer solid electrolyte according to claim 7, characterized in that: The surface of the cellulose paper-based polymer solid electrolyte is flat and smooth, and the cross section is a sandwich structure; the sandwich structure is composed of an intermediate layer of a cellulose membrane and a polymer solid electrolyte, and the polymer solid electrolyte is located on both sides of the intermediate layer.

9. The cellulose paper-based polymer solid electrolyte according to claim 7, characterized in that: The thickness of the cellulose paper-based polymer solid electrolyte is 70 μm~75 μm.

10. A solid-state lithium metal battery, characterized in that: The invention is made of a negative electrode shell, a spring sheet, a gasket, a negative electrode lithium sheet, the cellulose paper-based polymer solid electrolyte according to claim 7, a positive electrode sheet and a positive electrode shell.

Citation Information

Cited By

  • Paper-based solid electrolyte with high conductivity and flame retardant property as well as preparation method and application of paper-based solid electrolyte

    CN120497424A

  • A paper-based solid electrolyte with high electrical conductivity and flame retardancy, and its preparation method and application

    CN120497424B

  • Fluorinated acrylate reference solid electrolyte with hydrogen bond anchoring and amide dissociation as well as preparation method and application of fluorinated acrylate reference solid electrolyte

    CN121076238A

  • PVDF (Polyvinylidene Fluoride) composite cellulose paper-based solid polymer electrolyte as well as preparation and application methods thereof

    CN121584032A